MAHIR Model: Redefining Scout Leadership Competence - Mundzir, Ahmad; Marlina, Lina (Indonesian Scientific Publication, 2026)
In Indonesia, Scout leadership has traditionally been defined through administrative certification programs such as the Basic and Advanced Training Courses (KMD and KML). However, certification alone does not necessarily represent the full range of competencies required for guiding, inspiring, and nurturing young people. This article introduces the MAHIR Model as a conceptual framework to redefine Scout leadership competence beyond administrative recognition. MAHIR stands for Mentorship, Active Learning Facilitator, Humanistic, Inspirational, and Service-Oriented. These five dimensions integrate core Scouting values with contemporary theoretical perspectives including Positive Youth Development, Self-Determination Theory, Social and Emotional Learning, psychological safety, and servant leadership. The model emphasizes a shift from certificate-based recognition to competency-based evaluation, focusing on pedagogical quality, character formation, and measurable leadership performance. A mixed-method validation approach is proposed, combining Likert-type self-assessments with structured observation rubrics to capture both perceptual and behavioral aspects of leadership. The article contributes theoretically by redefining the meaning of qualified Scout leadership, methodologically by proposing an empirically testable framework, and practically by offering a pathway to professionalize Scout leadership in Indonesia’s non-formal education system.